Validitas Lembar Aktivitas Peserta Didik (LAPD) dengan Pendekatan Contextual Teaching and Learning untuk Meningkatkan Keterampilan Proses Sains Peserta Didik pada Materi Hidrolisis Garam Fase F - Wahyuni Wulandari; Rusmini Rusmini (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA DAN SAINS, 2026)
This study aims to develop and validate Student Activity Sheets (LAPD) using a contextual teaching and learning approach to improve students' science process skills on the topic of salt hydrolysis. This type of research uses Research and Development (R&D) with the 4D development model (Define, Design, Develop, and Disseminate), which is limited to the Develop stage. The Define stage includes front-end analysis, student analysis, task analysis, and concept analysis. The Design stage includes media selection, format selection, initial design, and preparation of science process skills tests. The Develop stage involves assessing the LAPD based on content validity and construct validity using a Likert scale (1-5), conducted by two chemistry lecturers and one chemistry teacher. The LAPD is considered valid if it receives a mode score from all validators with the criteria of "good" or "very good". The research results indicate that the LAPD received a “very good” category for content validity, which includes the suitability of the material with learning outcomes and learning objectives, the accuracy of knowledge concepts, the appropriateness of answer keys, the alignment of material with cognitive levels, consistency with the learning model, and indicators of science process skills. Construct validity, which encompasses language, presentation, graphics, and features, also received a “very good” category. Overall, the validation results show that the LAPD with a contextual teaching and learning approach is considered valid and feasible to use to enhance students' science process skills in the topic of salt hydrolysis.